Caracterização das fases de desenvolvimento de células gigantes induzidas por Meloidogyne exigua em raiz de seringueira (Hevea brasiliensis Muell. Arg.) - Corrêa, C. F. [UNESP]; Rodella, R. A. [UNESP] (My University, 2002)
The developmental phases of giant cells induced by root-knot nematodes (Meloidogyne exigua) in rubber plant (Hevea brasiliensis) root were studied in relation to its number and size evaluated in eight sample dates. The results were subject to cluster analysis and principal component analysis. Sample dates were clearly distinct regarding giant cell development. As a result, the nematode infestation cycle was characterized by the following sequential phases: initial, equilibrium, choice and final.
Characterization of developmental phases of giant cells induced by Meloidogyne exigua in rubber plant (Hevea brasiliensis Muell. Arg.) root
Keywords: Histopathology; Multivariate analysis; Root-knot nematodes; Hevea brasiliensis; Meloidogyne; Meloidogyne exigua; Meloidogyne javanica; Nematoda